Socio Cultural Study of Communities for Biodiversity Conservation - Sunarminto, Tutut (Media Konservasi, 2011)
An understanding of human behaviour is one of the key factors for a successful biodiversity conservation, because man is the major subject in natural resources management. Human ecology and rural sociology help to reveal more about human behaviour to support biodiversity conselvation of natural rcsources.